The experiences of remaining nurse tutors during the transformation of nursing colleges - Ellie C. van Dyk; Gisela H. van Rensburg; Juanita E. Tjallinks (AOSIS, 2009)
The transformation of public services and education in South Africa is part of the political and socio-economic transition to democracy. Changes are occurring in every field, including that of the health services. A qualitative study was undertaken to investigate the experiences of the remaining nurse tutors at a school of nursing during the transformation of nursing colleges and the downsizing of staff. The study on which this article is based was aimed at describing the experiences of those individuals undergoing changes in their work environment, with the purpose of contributing to recommendations regarding the 'survival' of transformation and the downsizing of the workplace. Three themes emerged by way of the narrative descriptions and unstructured in-depth interviews conducted during the study. The first theme, revolving around affective responses, relates to the emotions, low morale, depressive moods and anxiety caused by the transformation and downsizing. The second theme, relating to the cognitive and perceptual view of transformation, revealed the thoughts, beliefs, and opinions of the remaining nurse tutors regarding the change. The perceptions of, and opinions about how, nursing education and human dignity have been affected by this transformation were also expressed. The third theme consists of the coping responses made by the nurse tutors in the form of work-related personal and social adjustments to the transformation of the nursing colleges. The maintenance of ongoing communication and participation by the nurse tutors, as part of their counselling process, is advised. Opsomming Die transformasie van die openbare dienste en onderwys in Suid-Afrika vorm deel van die politieke en sosio-ekonomiese oorgang tot demokrasie. Veranderinge vind plaas op elke terrein, wat ook gesondheidsdienste insluit. 'n Kwalitatiewe studie is onderneem om die belewing van die oorblywende verpleegdosente verbonde aan 'n verplegingskool te ondersoek te midde van die transformasie van verpleegkolleges en personeelvermindering wat plaasvind. Die studie het beoog om die belewing van indiwidue gedurende veranderinge by hul werksomgewing te beskryf, met die doel om by te dra tot aanbevelings wat personeel sou kon help om transformasie en personeelvermindering by die werkplek te 'oorleef'. Drie temas het uit die narratiewe beskrywings en ongestruktureerde in-diepte onderhoude na vore gekom. Die eerste tema, affektiewe response, sluit in emosies, lae moraal, depressiewe gemoed en angs wat deur transformasie en personeelvermindering veroorsaak word. Die tweede tema, kognitiewe en perseptuele betekenis, toon die gedagtes, oortuigings en menings van oorblywende verpleegdosente rakende die transformasie en personeelvermindering aan. Persepsies en opinies van hoe verpleegonderrig en menslike waardigheid geraak is, is ook weergegee. Die derde tema toon die hanteringsresponse, wat werkverwante, persoonlike en sosiale aanpassings van verpleegdosente gedurende die transformasie van verpleegkolleges beskryf. Daar word aanbeveel dat goeie kommunikasie en deelname in die berading van verpleegdosente gehandhaaf word.